The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/adsc.201901421
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Reaction of p‐Quinone Monoacetals, Amines and Diarylphosphine Oxides to Afford m‐(Phosphinyl)anilides

Abstract: The three‐component reaction of p‐quinone monoacetals, amines and diarylphosphine oxides is developed to afford m‐(diarylphosphinyl)anilides in moderate to high yields. The reaction may proceed via a process involving phospha‐nucleophilic addition to an iminoquinone acetal intermediate and/or carbonyl‐amine condensation with a phosphinyl enone intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…14 16 For example, Qu et al reported the three-component couplings of pyrrolidin-3-ol and p -benzoquinone monoacetal with vinyl- and arylboronic acids to selectively afford cis -2-substituted 3-pyrrolidinols. 16a Recently, we 14` e f g h and others 16b c reported a series of transformations involving QMAs, primary amines/amino acids, with/without another nucleophile to afford 3-aminoarylphosphoryl products, N -aryl-2-arylpyrrolidines, octahydrodipyrroloquinolines, and bridged oxocyclic compounds selectively. Here, we report our results on two sets of MCRs involving QEs/QMAs as both the arylation components and the oxidants, and H-phosphine oxides/naphthols as the terminating nucleophiles to accomplish the process of N -arylation of the simple pyrrolidine with α-phosphinylation or arylation.…”
Section: Table 1 Optimization Of Reaction Conditions Fo...mentioning
confidence: 99%
“…14 16 For example, Qu et al reported the three-component couplings of pyrrolidin-3-ol and p -benzoquinone monoacetal with vinyl- and arylboronic acids to selectively afford cis -2-substituted 3-pyrrolidinols. 16a Recently, we 14` e f g h and others 16b c reported a series of transformations involving QMAs, primary amines/amino acids, with/without another nucleophile to afford 3-aminoarylphosphoryl products, N -aryl-2-arylpyrrolidines, octahydrodipyrroloquinolines, and bridged oxocyclic compounds selectively. Here, we report our results on two sets of MCRs involving QEs/QMAs as both the arylation components and the oxidants, and H-phosphine oxides/naphthols as the terminating nucleophiles to accomplish the process of N -arylation of the simple pyrrolidine with α-phosphinylation or arylation.…”
Section: Table 1 Optimization Of Reaction Conditions Fo...mentioning
confidence: 99%
“…[23][24][25][26][27] Recently, various 'greener' pathways as alternatives to traditional chemical syntheses and transformations have been invented in diverse fields of organic chemistry, including organophosphorus chemistry, to attain greater sustainability through newer concepts. [28][29][30][31][32][33] The practice of 'green' chemistry comprises many aspects. Among them, designing solvent-free techniques is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…With a recent interest in developing new synthetic methods for nitrogen‐ and phosphorus‐functionalized aromatics by the use of QMAs as arylation reagents, we have reported the three‐component reactions involving QMAs, amines or α‐amino acids with the third trapping reagents [16] . The reactions, presumably involving selective generation of iminoquinone acetal intermediates from the ketone‐amine condensation of QMAs, provide a platform to access a diversity of functionalized products via selective interceptions of the intermediates [16d–g,17] . These findings invoke our interest in exploring catalytic annulations of QMAs for the synthesis of bridged ring systems.…”
Section: Introductionmentioning
confidence: 99%